Incentive Complexity, Bounded Rationality, and Effort Provision - Abeler, Johannes; Huffman, David; Raymond, Collin (American Economic Review, 2025)
Using field and laboratory experiments, we demonstrate that the complexity of incentive schemes and worker bounded rationality can affect effort provision. This is because some attributes of the incentives become opaque; that is, workers do not take them into account. In our setting, workers overprovide effort relative to a fully rational benchmark, improving efficiency. We identify contract features, and facets of worker cognitive ability, that matter for opacity. We find that even relatively small degrees of opacity can cause large shifts in behavior. Our results illustrate important implications of complexity and bounded rationality for designing and regulating workplace incentive contracts. (JEL C90, D21, D91, J22, J31, J41)